HYBRID TECHNIQUE FOR SOFTWARE CODE CLONE DETECTION (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2012)
Software Clone detection is one of the hottest research area that helps in detecting duplicate code from an applications. The research has shown that 5% to 20% of software systems can contain duplicated code that is generated by simply copying the existing program code and pasting with or without minor modifications. Cloning creates problem when a bug is found in one code segment that was copied and pasted at several locations earlier. The objective of this study is to analyze the working of hybrid clone detection technique that design and analyze a hybrid technique for detecting software clone in an application. We will combine metric approach with text base (line of code) technique for the above said reason. A model will be designed to automate the concept of clone detection.